The mediating effect of organizational ethical climate on the relationship between ethical leadership and workplace deviance public healthcare sector of Pakistan - Yasir, Muhammad (2017)
Over the years, increased level of deviant behavior among the employees of public sector organizations has been observed. The situation is worst in the public healthcare sector of Pakistan, where numerous incidents of employee deviant behavior have been reported recently. This scenario is compelling scholars and practitioners to find appropriate solutions to address this issue. Researchers agree that establishing an organizational ethical climate can help in reducing workplace deviance. However, limited studies exist on the role of ethical leadership in establishing an organizational ethical climate in order to minimize employee deviant behavior in the public healthcare sector. Thus, to fill this gap, the current study aims to investigate the interrelationship between ethical leadership and workplace deviance with the mediating role of organizational ethical climate in the context of public healthcare sector. This research employed survey strategy, using the quantitative method with a cross-sectional research design, and with multi-stage sampling technique. 289 usable questionnaires were collected from doctors and nurses in the public healthcare sector of Pakistan. Statistical Package for Social Sciences (SPSS) was utilized to assess the data in terms of coding, missing data, outliers, normality, pilot testing and common method bias test and to compute preliminary data analysis such as mean, standard deviation and frequencies for each variable and to conduct Exploratory Factor Analysis (EFA) on ethical leadership and workplace deviance. Moreover, Structural Equation Modeling (SEM) was conducted using Analysis of Moment Structures (AMOS) in order to test the hypothesized model and determine the direct and indirect effects. Results of this research revealed that ethical leadership negatively influenced workplace deviance. Moreover, ethical leadership had a positive effect on organizational ethical climate. Results of the study showed that organizational ethical climate had a negative relationship with workplace deviance. This research also found that organizational ethical climate mediated the relationship between ethical leadership and workplace deviance. Thus, this research identified the significance of ethical leadership behavior which assists in establishing an ethical organizational climate, leading towards less likelihood of the emergence of workplace deviance. Therefore, top management of the public healthcare sector of Pakistan should seek to select and develop ethical leaders, establish an ethical organizational climate, thereby reducing the emergence of workplace deviance.